The marketing mix strategy to promote local Malaysian food: from the perspective of SME restaurant business / Arina Aqilah Sukur, Norzuwana Sumarjan and Mohd Hairi Jalis - Sukur, Arina Aqilah; Sumarjan, Norzuwana; Jalis, Mohd Hairi (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
Marketing strategy is essential for all types and sizes of restaurant businesses, including Small and Medium Enterprises (SMEs), to obtain local market share and profit. Studies showed that an effective marketing strategy can help a restaurant differentiate itself from its competitors by emphasizing its distinct products, thereby increasing its visibility, and attracting more customers. Customers are less likely to return if they do not appreciate their dining experience, regardless of how well the restaurant provides quality food and service and employs strategic marketing to promote itself. In contrast, a positive experience may encourage positive word-of-mouth marketing and build a strong brand image. Therefore, this paper aims to analyze the implementation of marketing mix in promoting local Malaysian food through interviews with the SME restaurant businesses owners. Data will be transcribed, coded, and analyzed for themes. Based on the concept and understanding of marketing mix strategy, this paper further discusses on the marketing mix strategy concept and application within the local Malaysian food restaurant setting. This helps to provide a better understanding on relevant marketing strategies and articulate the principal idea of marketing mix and its role towards promoting and sustaining the SME restaurants in Malaysia.